Das Diktat der Toten - Zoë Ghyselinck (Recherches Germaniques)
This article studies contemporary literary representations of communication with the dead as forms of unnatural narration. In Hagar Peeters’s novel Malva (2015), a dead child character-narrator, Malva, posthumously attempts to regain her voice which was suppressed by her father. This paper aims to deepen our understanding of the emancipatory potential of Malva’s narration, by approaching the concept of mediation in this necrodialogue. The article links recent approaches to unnatural narration to a literary tradition of communication with the dead by linking them to insights into the intersections between spiritualist, especially mediumistic discourse on the one hand and media development on the other. It argues that the use of human and technical forms of mediation both helps and hinders Malva’s communication of her story, as the mediation of dead voices reveals a complex interaction between authorship and mediumship and denies its own possibility.